2022
DOI: 10.1590/1984-0462/2022/40/2020234
|View full text |Cite
|
Sign up to set email alerts
|

Use of new technologies and promotion of breastfeeding: integrative literature review

Abstract: Objective: To identify the most used social networks and the most consumed contents by women seeking support and further understanding of breastfeeding/breast milk. Data source: An integrative literature review was performed using the Psychology & Behavioral Sciences Collection, MEDLINE Complete, CINAHL Complete, MedicLatina, Academic Search Complete and ERIC databases. The search was conducted in April, 2020. The inclusion criteria were: publications in Portuguese, English or Spanish with several keyword… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
(46 reference statements)
1
2
0
2
Order By: Relevance
“…(16). Similar conclusions were found by Garcia et al who, in their research, identified how new technologies and social media help women to clear doubts of traditional health services, promote breastfeeding and create new areas to get in touch with mothers (17).…”
Section: Discussionsupporting
confidence: 81%
“…(16). Similar conclusions were found by Garcia et al who, in their research, identified how new technologies and social media help women to clear doubts of traditional health services, promote breastfeeding and create new areas to get in touch with mothers (17).…”
Section: Discussionsupporting
confidence: 81%
“…Corroborando com práticas inovadoras, um estudo de revisão integrativa sobre amamentação identificou a utilização de redes sociais como alternativa à abordagem em consultório, desde que as informações sejam pautadas na ciência e clinicamente sólidas. As redes sociais emergiram como meio para a disseminação de informações, como forma de partilhar as experiências, sendo um meio de fácil acesso de informação, de socialização com outras mulheres envolvendo desde ajuda emocional até encorajamento (18) .…”
Section: Discussão Estratégias Utilizadas Nas Práticas Educativas Em ...unclassified
“…Ainda, o estabelecimento de atividades educativas não só com a gestante, mas com sua rede de apoio (mãe, sogra, irmã, etc) emergiu como relevante, devido serem fontes de influência sobre a adesão ao AM (18) . Nesta mesma linha observa-se a partir dos achados deste estudo incremento de práticas de educação ampliada com envolvimento da gestante e rede de apoio que culminaram no esclarecimento de dúvidas, na desconstrução de mitos e crenças sobre amamentação (11) .…”
Section: Discussão Estratégias Utilizadas Nas Práticas Educativas Em ...unclassified
“…Moreover, social media is a useful platform for new or expecting mothers to socialize and gain emotional support from peers. 54 Given the flexibility and convenience modern technology provides, person-centered technological innovations may be an optimal solution to address gaps in care. However, the $55 billion formula industry invests money into deceitful and exploitive apps, social media profiles, and peer support groups that endorse and advertise formula usage.…”
Section: Technological Innovationsmentioning
confidence: 99%
“…NewMomHealth.com/SaludMadre.com are free websites designed by researchers, clinicians, and mothers that contains information and resources on a variety of postpartum domains including breastfeeding. Moreover, social media is a useful platform for new or expecting mothers to socialize and gain emotional support from peers 54. Given the flexibility and convenience modern technology provides, person-centered technological innovations may be an optimal solution to address gaps in care.…”
Section: Innovation In Lactation Supportmentioning
confidence: 99%